Análise proteômica diferencial da fração periplasmática das estirpes A, B e C de Xanthomonas spp. que diferem na patogenicidade e espectro de citros hospedeiros - Zandonadi, Flávia da Silva (Universidade Federal de São Carlos, 2012)
The aim of this work was to perform differential proteomic analysis of the periplasmic protein profiles of the genome strains A, B and C of Xanthomonas spp, which differ in pathogenicity and host range of citrus. The strain Xanthomonas citri subsp. citri (Xac) is the most virulent and infects all types of citrus, while the strain B (Xanthomonas fuscans subsp. aurantifolii, Xau-B) is less virulent and the strain C (Xanthomonas fuscans subsp. aurantifolii, Xau-C) has a unique citrus-host. The comparative proteomic analysis of Xau-B and Xau-C in relation to Xac can reveal genes and proteins involved in pathogenicity and host range of citrus, respectively. The strains A (Xanthomonas citri subsp. citri, Xac) and C (Xanthomonas fuscans subsp. aurantifolii, Xau-C) were grown in XAM-1, which is known to be a pathogenicity-inducing medium for Xac, and in a non-inducing pathogenicity (Nutrient Broth, NB). Proteins from both types (grown in triplicate using both media), were separated by bidimensional electrophoresis (2DPAGE) and the gels were stained using Coomassie Brilliant Blue R-250 and documented. A comparative analysis of the protein profiles of Xac and Xau-B, and Xac and Xau-C, grown in the same culture medium, was performed using ImageMaster Platinum software (GE Healthcare). Statistical analysis (ANOVA) revealed a large number of periplasmic proteins that presented type-specific or differential expression between the two bacteria. For the comparison between Xac and Xau-B we used the twodimensional Xau-B gels of periplasmic proteins obtained by Carnielli (2011). The differential spots between Xac and Xau-C, Xac and Xau-B that showed a significant differential expression (p <0.05) were isolated from gels and identified by ESI-QUADTOF mass spectrometry (LNBio, Campinas-SP), employing Xac, Xau-B and Xau-C databases. Several differentially expressed proteins between strains were identified for the different conditions studied, showing that some of them were strain-specific (approximately 10) while others were expressed in all strains, differing only in intensity. Those proteins potentially related to pathogenicity and citrus host were quantified using the software Scaffold v. 3.0, for the mass spectrometry data.The results showed that Xac, Xau-B, and Xau-C had remarkable differences between the periplasm protein profiles for both conditions, even under conditions of no induction of pathogenicity. The proteomics approach showed that even though the strains showed a different pattern of protein expression, the sequences of genes related to the differential proteins are present in all strains. Based on the proteomic analysis, proteins that showed remarkable differential expression between the genome strainswere selected, and its expression was evaluated by Western blot in periplasmic fraction of the bacteria. The data obtained in the the comparative proteomic analysis for the superoxide dismutase corroborated most quantitative results generated by the software Scaffold. This work showed that the proteomic analysis, combined with quantitative analysis tools, is an important tool that comes to complement genomic investigations designed to differentiate the species of Xanthomonas spp.
Keywords: Cancro cítrico; Xanthomonas citri subsp. citri; Xanthomonas fuscans subsp. aurantifolii tipo B; Xanthomonas fuscans subsp. aurantifolii tipo C; Fitopatogenicidade; Análise proteômica diferencial; Eletroforese bidimensional; Bioquímica; Xanthomonas; Proteômica; Eletroforese; Citrus canker; Xanthomonas citri subsp. Citri; Xanthomonas fuscans subsp. aurantifolii type B; Xanthomonas fuscans subsp. aurantifolii type C; Phytopathogenicity; Differential proteomic analysis; Two-dimensional electrophoresis; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS